Situation awareness in sea kayaking: towards a practical checklist. Issue 3 (3rd July 2017) - Aadland, Eivind; Vikene, Odd Lennart; Varley, Peter; Moe, Vegard Fusche
ABSTRACT: Ever-changing weather and sea conditions constitute environmental hazards that sea kayakers must pay attention to and act upon to stay safe. The aim of this study was to propose a tool to aid sea kayakers' situation awareness (SA). We developed a checklist guided by theory on the concept of SA and expert problem detection, judgement and decision-making, along with knowledge concerning previous incidents and important risk factors in sea kayaking. The checklist consists of two parts: a guide to how paddlers can improve their SA and decision-making skills, and an overview of what critical factors should be evaluated before and during a sea kayak trip. We argue that the checklist may improve risk assessment and management among sea kayakers, help to prevent distress and future incidents, and ultimately potentially save lives. Finally, we wish to stimulate debate concerning risk management in sea kayaking and outdoor education.